2018
DOI: 10.1515/jomb-2017-0048
|View full text |Cite
|
Sign up to set email alerts
|

Potential Immune Biomarkers in Diagnosis and Clinical Management for Systemic Lupus Erythematosus

Abstract: SummaryBackgroundThere is still no reliable, specific biomarker for precision diagnosis and clinical monitoring of systemic lupus erythematosus. The aim of this study was to investigate the importance of the determination of immunofenotypic profiles (T, B lymphocytes and NK cells) and serum cytokine concentrations (IL-17 and IFN-alpha) as potential biomarkers for this disease.MethodsThe study included 55 patients with SLE and 25 healthy controls. The proportion of T, B, NK cells were assessed in peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…From a total of 139 assays reported,7–123 most of them used quantitative PCR (qPCR), immunoassays or microarrays. Most of the studies reported markedly increased IFN-I pathway activation in SLE compared with controls, but diagnostic statistics were scarcely reported and study designs did not usually recruit a prediagnosis population (online supplemental table 1).…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 139 assays reported,7–123 most of them used quantitative PCR (qPCR), immunoassays or microarrays. Most of the studies reported markedly increased IFN-I pathway activation in SLE compared with controls, but diagnostic statistics were scarcely reported and study designs did not usually recruit a prediagnosis population (online supplemental table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The observed decrease in T reg cell percentage may be a recovery indicator of lupus nephritis, apart from renal pathological changes and the serum concentration of anti-dsDNA antibody. Increased T reg cell percentage may be a response to overwhelming inflammation,[ 18 ] and a decrease with concurrently reduced Foxp3 expression may indicate amelioration after treatment. Furthermore, the decreased concentrations of IL-6 and IFN-γ indicated declined levels of inflammatory mediators and pro-inflammatory factors in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…SLE can affect both sexes, but the incidence in females especially at the childbearing age is higher than the males with a ratio of 9 women for each man suffering from SLE [6]. SLE is a chronic inflammatory disease characterized by heterogeneous clinical manifestations and immunological abnormalities, especially the overproduction of autoantibodies, primarily to the nuclear materials of the cell, complement activation, and the deposition of the circulating immune complexes (CIC) in various tissues leads to inflammatory [7][8][9]. Multiple mechanisms may be participated in the pathophysiology of SLE, comprising incomplete clearance of apoptotic and necrotic materials, abnormal exposure to autoantigens, hyperactivity of self-reactive B and T lymphocytes, and increased levels of B-cell stimulatory cytokines [10][11][12].…”
Section: Introductionmentioning
confidence: 99%